Effect of Yea Sacc1026 Supplementation on Feed Intake and Rumen Fermentation in Buffalo Calves during Summer Season - Singh, Harjap (Indian Journal of Animal Nutrition, 2018)
The study was carried out with eight apparently healthy male buffalo calves to study the effect of Saccharomyces cerevisae (Yea Sacc1026)supplementation on rumen microbial abundance during summer season. The animals were divided into three groups of four each. Group I (Pre-summer), Group II ( Summer control) and Group III ( Summer treatment). Same animals were used in pre-summer and summer control groups. The animals of Group III were supplemented with Yea Sacc1026 @ 1 bolus (consisting of 25 billion live yeast cells) / animal per day. The results revealed that there was significant (P